Drug addiction: self-perception of oral health - Eduardo Luiz Da-ré; Gabriel Ferreira Bello; Gabriela Pereira Silva; Leandro Araújo Fernandes; Daniela Coelho de Lima (Universidade de Fortaleza, 2015)
Objective: To report the self-perception of substance-abusing individuals who were in a recovery process regarding sociodemographic conditions and general and oral health. Methods: Descriptive cross-sectional study conducted in a recovery center for drug addiction in Alfenas, Minas Gerais, Brazil, in 2015, with 39 men aged over 18 years old. Data were collected using a semi-structured questionnaire that addressed: socioeconomic status, selfperception of general and oral health, access to dental care, relationship with the dentist, and other issues. In order to assess the self-perception of oral health, the variable was dichotomized into "satisfactory" and "unsatisfactory", which refer to what the individual acknowledges as a good or poor condition of oral health, using Fisher's exact test with 5% significance level. Results: Most frequent diseases were depression, 35.90% (n=14), insomnia, 35.9%, (n=14) and recurring headache (23.1%; n=9); however, 61.50% (n=24) of the participants reported not getting sick easily, which contrasts with their self-perception. Regarding oral health, only 30.50% (n=12) of the participants reported brushing their teeth three times a day; 53.80% (n=21) had dentinal hypersensitivity; 41.00% (n=16) had dry mouth and bad breath; 30.80% (n=12) claimed to have bruxism and reported having one or more loose teeth; 28.20% (n=11) reported clenching the teeth in an exaggerated way, and 33.30% (n=13) reported feeling tooth pain. Conclusion: The self-perception of individuals - under 30 years old, single, white or mulattos - regarding their general health was contradictory, as they rated it as good but have reported depression, insomnia and weight loss; additionally, oral health was considered poor with unsatisfactory conditions, which highlights the harmful effects of substance abuse.